Reassessing the need for carbon dioxide removal: moral implications of alternative climate target pathways - Lieske Voget-Kleschin; Christian Baatz; Clare Heyward; Detlef Van Vuuren; Nadine Mengis (Global Sustainability)
Abstract Non-technical summary Scenarios compatible with the Paris agreement's temperature goal of 1.5 °C involve carbon dioxide removal measures – measures that actively remove CO2 from the atmosphere – on a massive scale. Such large-scale implementations raise significant ethical problems. Van Vuuren et al. (2018), as well as the current IPCC scenarios, show that reduction in energy and or food demand could reduce the need for such activities. There is some reluctance to discuss such societal changes. However, we argue that policy measures enabling societal changes are not necessarily ethically problematic. Therefore, they should be discussed alongside techno-optimistic approaches in any kind of discussions about how to respond to climate change.